Quantum-sapiens: The quantum bases for human expertise, knowledge, and problem-solving - Steve J. Bickley; Ho Fai Chan; Sascha Leonard Schmidt; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2020)
In this contribution, we highlight the potential for quantum theories to reignite the art and science of expert systems and knowledge engineering. With their fundamental grounding in uncertainty and unpredictability, quantum concepts are able to expand theoretical and practical boundaries of research and exploration. We demonstrate the similarities between quantum concepts and expert systems, outlining five domains (Scientific Discovery, Creativity and Breakthrough Thinking; Complex Systems; Medical Sciences and Advice; Strategic Business Management; and Future of Sports) we regard as largely unexplored in popular accounts of quantum theory; as such, these are low hanging fruit for the application of quantum technologies.
Keywords: 330; Quantum; Expert Systems; Knowledge; Problem-Solving